Effects of variable resistance training within complex training on strength and punch performance in elite amateur boxers - Liu, Yongfu; Huang, Zijing; Zhou, Zixiang; Zhang, Liqin; Guo, Yuqiang; Chen, Chao (Frontiers in Physiology, 2024)
Objectives: This study explored the effects of six weeks of variable resistance training (VRT) and constant resistance training (CRT) within complex training, on muscle strength and punch performance.Methods: Twenty-four elite female boxers from the China National team were divided randomly between an experimental group (VRT) and a control group (CRT). Maximum strength of the upper and lower limbs, countermovement jump (CMJ) performance, and punch performance (single, 10s and 30s continuous) were assessed pre-and post-intervention.Results: VRT and CRT showed significant increases (p < 0.001) in the bench press (ES = 1.79 and 1.07, respectively), squat (ES = 1.77 and 1.10, respectively), and CMJ (ES = 1.13 and 0.75, respectively). The bench press (p < 0.05) and squat (p < 0.05) improved significantly more following VRT compared to CRT. Additionally, single punch performance (speed, force, and power) increased significantly in the experimental group (ES = 1.17 -1.79) and in the control group (ES = 0.58 -1.32), except for the lead punch force in the control group (p > 0.05, ES = 0.20). 10s continuous punch performance (number, speed, force, and power) increased significantly (both p < 0.05) in the experimental group (ES = 0.52 -1.65) and in the control group (ES = 0.32 -0.81). 30s continuous punch performance (number, force, and power) increased significantly increased significantly (both p < 0.05). However, no statistically significant differences were found between groups for punch performance.Conclusions: These findings provide evidence that VRT may improve maximum muscle strength in both upper and lower limbs, vertical jump and punch performance in elite amateur boxers.